(untitled) (Bangladesh Journal of Botany, 2020)
Eriobotrya fusca Kuan ex Gao & Idrees, belonging to the family Rosaceae, a new species from Yunnan Province, China is described and illustrated based on both morphological and molecular data. The new species resembles closely morphologically to E. salwinensis Hand.-Mazz., but differs from it by having elliptic-oblong or oblong-ovate leaves, fewer pairs of lateral veins (12 - 15), lanceolate bracteoles, absent of pedicels, peduncles ca. 10 mm long, both densely brown tomentose, suborbicular petals with emarginate apices, triangular sepals with acute apices, and styles that are connate at their base. The phylogenetic analysis based on nrDNA ITS sequences confirmed the distinctiveness of this new species.